Detection of ISSR markers linked to seed oil biochemical characteristics in castor (Ricinus communis L.) through association analysis - Darvishzadeh Reza (Genetika, 2016)
In major crops, panels of germplasm accessions have been assembled for allele mining at targeted candidate genes and for whole-genome association mapping studies. A germplasm collection of 60 genotypes belong to 12 castor accessions from six different provinces of Iran were evaluated for seven biochemical traits as important seed oil components and tested for significant association with the allelic profile of 16 ISSR primers. Study of population structure as a prerequisite for association analysis showed that there is six possible subgroups (K=6) in the studied population that also barplot results confirmed it. Mixed linear model (MLM) were used to discover marker/trait associations. As a result, 37 marker-trait significant associations (P≤0.05) were identified and a maximum number of marker-trait associations (27.03%) were identified for Stearic acid. The identified and associated markers are expected to be useful in marker-aided breeding of high oil content genotypes in castor.